Water Quality Characteristics of Batang Mahat Around PLTA Koto Panjang Dam - Permata Zahrani Hedista; Muhammad Fauzi; Adriman Adriman (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
Batang Mahat River is one of the rivers which empties to PLTA Koto Panjang Dam. Batang Mahat estuary around PLTA Koto Panjang Dam is one of the fishing grounds. This study was aimed to obtain information about the water chemical and physical characteristics and biology (plankton) Batang Mahat around PLTA Koto Panjang Dam. This research was conducted in March-May 2019 The observation stations were determined using the purposive sampling method and then divided into three observation stations. Sampling was carried out 3 times with an interval of 2 weeks. Data analysis was performed descriptively. The results showed the water quality of Batang Mahat around the PLTA Koto Panjang Dam are as follows: temperature 31-32oC, tranparancy 2.00-2.31 m, pH 6, dissolved oxygen 4.32-6.90 mg/L, CO2 0.39-3.9 mg/L, nitrate 0.0021-0.1375 mg/L, and phosphate 0.0177-0.0774 mg/L. The results of the study found as many as 23 species. Plankton which belongs to 7 classes, namely: Bacillariophyceae, Chlorophyceae, Dinophyceae, Euglenophyceae, Synurophyceae, Magnoliopsida and Maxillopoda. Plankton abundance ranges from 20,000-64,250 ind/L. The diversity index ranges from 1.88-2.83. The similarity index ranges from 0.48-0.95 and the dominance index ranges from 0.19-0.36. Water quality Batang Mahat based on the environmental index is classified as moderate.